1997
DOI: 10.1143/ptp.98.1123
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Effects and Compressional Properties of Nuclear Matter in Cutoff Field Theory

Abstract: Including the vacuum effects, the compressional properties of nuclear matter are studied in the cutoff field theory. Under the Hartree approximation, the low-energy effective Lagrangian is derived in the framework of the renormalization group methods. The coefficients are determined in a way where the physical results hardly depend on the value of the cutoff which is conveniently introduced into the theory. It is shown that, to reproduce the empirical data of the nucleus incompressibility, the compressibility … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Also we must determine two coefficients D 5 and D 6 phenomenologically, to remove the Λ-dependence which is of the order of Λ −2 . In the references [30] and [31], we showed that D 5 and D 6 could be determined, if the effective nucleon mass M * 0 and the incompressibility K were given in addition to the saturation conditions. (Here, the subscript 0 denotes that the corresponding physical quantity is the one at the normal density ρ 0 . )…”
Section: Effective Lagrangian In the Hartree Approximationmentioning
confidence: 98%
See 3 more Smart Citations
“…Also we must determine two coefficients D 5 and D 6 phenomenologically, to remove the Λ-dependence which is of the order of Λ −2 . In the references [30] and [31], we showed that D 5 and D 6 could be determined, if the effective nucleon mass M * 0 and the incompressibility K were given in addition to the saturation conditions. (Here, the subscript 0 denotes that the corresponding physical quantity is the one at the normal density ρ 0 . )…”
Section: Effective Lagrangian In the Hartree Approximationmentioning
confidence: 98%
“…Referring to our previous work [30,31], we introduce a low-energy effective Lagrangian in the σ-ω model using the Hartree approximation.…”
Section: Effective Lagrangian In the Hartree Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…For the highenergy physics near the limitation of the theory of the particle physics, Lepage [8] proposed to use the extended effective action (Lagrangian) to eliminate such a dependence on cutoff which is by hand introduced into the theory, rather than to search the phenomenologically favorable cutoff and regulator (or form factor). In the series of papers [9,10,11], we have studied nuclear matter properties and the vertex corrections in the framework of the cutoff field theory, eliminating the cutoff dependence by using the Lepage's method.…”
Section: Introductionmentioning
confidence: 99%